Desmoplastic Fibroblastoma in Maxillary Alveolar Bone Mimicking An Odontogenic Lesion: A Novel Case Report with Review of Literature - Zohreh JAAFARI-ASHKAVANDI; Mehdi YASAMIN SHIRAZI; Sepideh ASSAR (Federation of Turkish Pathology Societies, 2018)
Desmoplastic fibroblastoma (Collagenous fibroma) is a rare benign soft tissue tumor that disseminates widely and can be intramuscular or subcutaneously. There are seven reported cases in the oral cavity so far. We reported a novel case of collagenous fibroma that has been found in the anterior part of maxilla in a 58-year-old woman as an intraosseous radiolucent lesion that has been discovered during routine radiography. Histopathologically, spindle and stellate-shaped fibroblasts in a collagen-rich stroma as well as binucleated and multinucleated fibroblasts with prominent nucleoli were seen. Desmoplastic fibroblastoma could be found in jaw bones and excision of the lesion is curative, and no aggressive growth has been reported.